Efficacy and safety of antiemetic regimens for highly emetogenic chemotherapy-induced nausea and vomiting: A systematic review and network meta-analysis. (April 2023) - Filetti, Marco; Lombardi, Pasquale; Giusti, Raffaele; Falcone, Rosa; Scotte, Florian; Giannarelli, Diana; Carcagnì, Antonella; Altamura, Valeria; Scambia, Giovanni; Daniele, Gennaro
Highlights: Chemotherapy-induced nausea and vomiting (CINV) represent an important issue in clinical practice. Integrating olanzapine in the antiemetic regimens offer the highest performance in terms of complete control of CINV. 3-drug NK-free regimen represents a valid treatment to be considered when a 4 drug regimen is not available. Abstract: Background: Several regimens have been introduced in clinical practice in the last twenty years to treat chemotherapy-induced nausea and vomiting (CINV). However, direct comparative data remain insufficient, as many new regimes lack head-to-head comparisons. In this study, through an indirect comparison, we overcome this limit by providing the most up-to-date estimate of the efficacy and safety of all combinations used for HEC-induced nausea and vomiting. Patients and methods: We retrieved randomized controlled trials (RCTs) published in Pubmed, Embase, and Cochrane Library until June, 30th 2022. We included phase II-III RCTs, including adults with any cancer receiving HEC, and compared different antiemetic regimes to prevent CINV. The primary outcome was the overall complete response (defined as the absence of vomiting and of the use of rescue drugs from 0 to 120 hrs since chemotherapy); secondary outcomes were acute (absence of vomiting and use of rescue medicine 0–24 hrs after chemotherapy) and delayed (24–120 hrs) response and adverse events. Results: A total of 53 RCTs enrolling 22 228 patients were included. We classified the different antiemetic regimes into 21 different groups. Overall, 3- or 4-drug regimens containing a combination of dexamethasone, 5HT3 antagonists, mirtazapine or olanzapine with or without NK antagonists, yielded the highest probability to be the most effective regimen in terms of complete response. Regimens containing a combination of dexamethasone and 5-HT3 antagonist have the lowest probability of being the most effective regimen in terms of complete, acute, and delayed response. Conclusion: In our network meta-analysis, 4-drug regimens with olanzapine displayed the highest probability of efficacy in terms of complete response. A 3-drug regimen with olanzapine represents a valid option in a limited resource context.